Clinical and molecular profiling of EGFR-mutant lung adenocarcinomas transformation to small cell lung cancer during TKI treatment - Chen, Yongxia; He, Mengye; Dai, Zhengfeng; Wang, Yina; Chen, Jing; Wang, Xiaoting; Dong, Xiao; Huang, Jianfei; Ruan, Jian; Zhang, Xiaochen; Shen, Peng; Jia, Yunlu (Frontiers in Oncology, 2023)
Introduction Small cell lung cancer (SCLC) transformation serves as a significant mechanism of resistance to tyrosine kinase inhibitors (TKIs) in advanced non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutations. To address this clinical challenge, we conducted a retrospective analysis at Zhejiang University School of Medicine, the First Affiliated Hospital, focusing on patients with EGFR sensitizing mutations. Methods A total of 1012 cases were included in this retrospective analysis. The cohort primarily consisted of patients with EGFR sensitizing mutations. Biopsy-confirmed small cell transformation was observed in seven patients, accounting for 0.7% of the cases. All patients in this subset were initially diagnosed with stage IV adenocarcinoma (ADC), with four cases classified as poorly differentiated and three as moderately to poorly differentiated ADC. EGFR exon 19 deletions were identified in five of these cases. Next-generation sequencing (NGS) was performed on seven cases, revealing mutations in the tumor protein p53 (TP53) gene in four cases and loss of the retinoblastoma1 (RB1) gene in three cases. Results The median duration from the initial diagnosis to small cell transformation was 35.9 months (interquartile range: 12.1–84 months). Following small cell transformation during EGFR inhibition, all patients received etoposide/platinum-based treatment, leading to a median progression-free survival (PFS) of 4.7 months (interquartile range: 2.7–10.1 months). Notably, most patients in this series had poorly differentiated adenocarcinomas at the outset. TP53 mutations and RB1 loss were common genetic alterations observed in patients with small cell transformation in this cohort. Discussion The findings underscore the clinical significance of SCLC transformation as a resistance mechanism to EGFR TKIs in NSCLC with EGFR mutations. The observed genetic alterations, including TP53 mutations and RB1 loss, suggest potential associations with the transformation process and warrant further investigation. Understanding the genetic landscape and clinical outcomes in patients experiencing small cell transformation can contribute to improved strategies for managing resistance in EGFR-mutant NSCLC.